Factors associated with mortality in a population with acute kidney injury undergoing hemodialysis in Peru - Herrera-Añazco, Percy (2017)
Introduction: Patients with acute kidney injury (AKI) in developing countries are described in a profile of young age, with less comorbidities, with unifactorial, and with a lower mortality compared to patients in developed countries. Objective: To assess mortality in patients with acute kidney injury undergoing hemodialysis (HD) and its associated factors in a developing country setting. Methods: Retrospective study. Demographic, clinical, and mortality variables were collected from patients who presented AKI and underwent HD between January 2014 and December 2015 at a national reference hospital in Lima, Peru. Risk ratios (RR) and 95% confidence intervals (95%CI) were estimated through Poisson regressions. Results: Data from 72 patients with AKI that underwent HD were analyzed, 66.7% of them were < 64 years old, and 40.2% of all patients died undergoing HD. Crude analysis showed higher mortality among those who used vasopressors, but lower mortality among those with creatinine values > 8.9 mg/ dL. The adjusted analysis showed that having had a creatinine level of > 8.9 mg/ dL, compared to a creatinine level of < 5.2 mg/dL at the time of initiating HD, was associated with 74% less probability of death. Conclusion: Four out of every ten AKI patients undergoing HD die. Higher levels of creatinine were associated with lower probability of mortality.